Analisis Pengaruh Debt Default, Kualitas Audit dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Ibrahim, Dicky Irawan, Fauzan, SE, M.Si (2016)
This research aims to test the influence of debt default , the quality of auditing and auditing opinion year earlier on revenue audit opinion going concern . Samples to research is manufacturing companies listed on the indonesian stock ( BEI ) starting in 2012 until 2014 about 231 a total of.The sampling uses the purposive sampling.Analysis techniques regression data using the logistics. The result showed that the value of the coefficients determined obtained value of 0,783 which means that 78.3 % audit opinion going concern can be explained by debt default , the quality of auditing and auditing opinion of the previous year , the rest of 21.7 % described by other variables outside a model research .Test the hypothesis of the results show that an audit opinion years earlier influences audit opinion going concern , while debt default and the quality of audit will not affect audit opinion going concern . Keywords: debt default , the quality of audit , audit opinion previous year , audit opinion going concern